Prognostic factors in stage IV oropharyngeal squamous cell carcinoma: the “punto” experience - Piccinini, Alessia; Alicandri-Ciufelli, Matteo; Ghidini, Angelo; Vincenti, Vincenzo; Ferri, teore; Presutti, Livio (Acta Biomedica Atenei Parmensis, 2016)
Purpose: Squamous Cell Carcinoma (SCC) of Oropharynx is often diagnosed in advanced stages. Treatment options have improved during recent years, however the choice of most appropriate treatment is still controversial. Prognostic factors can help to optimize the care. This study investigate the role of 9 potential prognostic factors, including HPV status, in Oropharyngeal SCC. Materials and Methods: Nine prognostic factors were investigated in a retrospective chart of 98 patients treated for stage IV SCC of Oropharynx from january 2006 to january 2012, including age (<60 or >60), gender, tumor subsite , histological grading, T stage, N stage, AJCC stage, BMI pre-treatment and HPV status. Moreover treatment modalities were compared and the data regarding the treatment factors, like radiotherapy technique and kind of chemotherapy were collected and compared. Primary endpoint was the impact of the prognostic factors on OS, DFS and DSS. Seconrdary endopoint were the impact of these factors on QOL and Toxicity. Results: On univariate analisys significant improved OS was associated with age < 60 (p= 0,004), grading G3 (p=0.003), BMI > 25 (p= 0.03), radiotherapy with IMRT/SIB IMRT technique (p=0,01) and AJCC stage IVa (p=0,01). No prognostic factor was associated to DFS improvement. Instead a significant improved DSS was associated with age <60 (p=0,01) , Grading G3 (p=0,04), T stage (p=0,02), AJCC stage IVa (p=0,03) and tonsil subsite (p=0.04). in the analysis of hazards ratios for OS age (HR 2.22; 95% CI 1.00-4.93; p=0.019), grading (HR 0.17; 95% CI 0.047-0.64 ; p= 0.008), AJCC stage (HR 4.81; 95% CI 1.34-17.2; p=0.016) and radiotherapy technique (HR 0.2; 95% CI 0.08-0.87; p=0.02) maintained significance, whereas BMI (HR 0.45; 95% CI 0.09- 2.2; p=0.3) did not. In the analysis for DSS only age (HR 2.22; 95% CI 1.22-7.81; p= 0.017) and grading (HR 0.11; 95% CI 0.02- 0.59; p=0.009) maintained significance. Conclusion: improved outcomes were significantly associated with lower age and tumor stage, grading G3, tonsil subsite, radiotherapy performed with IMRT technique, and BMI > 25.